Determinant of Employee Performance in Public Organization: The Case of Dessie City Municipality Office - Gebremichael Getahun Amha; Frewein Brhane (International Journal of Marketing & Human Resource Research, 2020)
Employee performance is significant role to achieve mission and vision of public, non-public and private organization. The main objective of this study is to examine the determinant of employee performance in the public organization; the case of Dessie city municipality office. In implementing of these internal practices; the office tested a problem of motivation practice, leadership, working environment and employee performance. This research problem was studied through the use of a descriptive and explanatory research design. To achieve the objective of the study 170 sample employees were selected from 312 total populations of municipality office employees through the stratified random sampling technique. The four independent variables incorporated for this study were training, motivation, leadership, and work environment. The study employed quantitative and qualitative approach and used primary data was collected using a questionnaire and secondary data obtained from offices annual report and BSC. The collected data was processed using SPSS v 20, and presented using frequency tables, bar charts, and pie charts, and analyze through descriptive and inferential data analysis techniques. The results have shown that the opinion of the respondent statistics analyses disagreed about motivation, leadership, and work environment and agree about training. Pearson correlation indicated that there is a high positive, and significant relationship between motivation and employee performance. Training and leadership were moderately positive relationship. The work environment had a small but definite positive linear relationship with employee performance. The findings of multiple linear regression training, motivation, leadership, and work environment greatly affected employee performance. This study recommended that the Dessie city municipality office better to give training to employee, utilize motivation practice, leadership, and work environment factors for increasing their employee performance. The Ethiopian government better to supported by the budget to solve problem of motivation and work environment.